Fatigue failure and energy evolution of double-stepped fissures contained marble subjected to multilevel cyclic loads: a lab-scale testing - Wang, Di; Luo, Zhixiong; Xia, Hongbo; Gao, Shangqing; Li, Peiliang; Li, Juzhou; Wang, Yu (Frontiers in Materials, 2023)
The instability of rock mass induced by the deterioration and failure of rock bridge is often encountered in hard rock engineering. Under engineering disturbance, a steep and gentle stepped sliding surface is prone to forming along the rock bridges between intermittent joints communicates, which directly controls the instability mode of engineering rock mass. In order to reveal the influence of fissure angle on the fatigue deterioration and energy evolution mechanism of stepped double-flawed hard rock, the multilevel cyclic loading mechanical test were carried out on flawed marble with fissure angle of 10°, 30°, 50° and 70° angles. The testing shows that rock strength, lifetime, peak strain and dissipated energy increase with increasing fissure angle and the increase rate of them becomes sharply in the high fatigue stage. In addition, the increase of dissipated energy accelerates with the increase of cyclic loading level, and shows a sudden increase trend in the last cyclic loading stage. When the joint fissure angle is 10°, the dissipated energy is the smallest and the dissipated energy is the largest at 70°. Moreover, a damage evolution model based on dissipated energy is established to describe the characteristics of damage accumulation. The model is in good agreement with the experimental data and reflects the nonlinear characteristics of damage accumulation.